Inovasi Flashmob Desa Ngrawan Kabupaten Semarang untuk Penguatan Pariwisata Berkelanjutan - Paranti, Lesa; Wiyoso, Joko; Prameswari, Nadia Sigi; Latifah, Ani Nur Auliyatun; Romayani, Wulan Suci Nur (Jurnal Bina Desa, 2025)
As a step to help Ngrawan Village in Semarang Regency develop sustainable tourism, the Community Service team from Universitas Negeri Semarang (UNNES) carried out an innovative activity. The aim was to create attractive art performances, such as flash mobs, to overcome the problem of a lack of innovation and regeneration of artists in the village. This activity employs a Community-Based Sustainability Development (CBSD) approach, which focuses on community empowerment. The methods used include training, mentoring, and evaluation. The main participants are members of the Karang Taruna ‘Omah Cikal’ youth organisation. As a result, a new flashmob dance themed ‘Ngrawan Menawan’ was successfully created and performed for the first time at the Ngrawan Art Festival on 30 August 2025. This innovation is expected to become an iconic dance in Ngrawan Village to strengthen local identity and unite communities from various hamlets. This activity proves that community empowerment through art can support sustainable tourism.